"The Real Thing:" Nominal Price Rigidity of the Nickel Coke, 1886-1959 - Daniel Levy; Andrew T. Young (Journal of Money, Credit, and Banking, 2004)
We report that the price of a 6.5oz Coke was 5 from 1886 until 1959. Thus, we are documenting a nominal price rigidity that lasted more than 70 years! The case of Coca-Cola is particularly interesting because during the 70-year period there were substantial changes in the soft drink industry as well as two World Wars, the Great Depression, and numerous regulatory interventions and lawsuits, which led to substantial changes in the Coca-Cola market conditions. The nickel price of Coke, nevertheless, remained unchanged. We find that this unusual rigidity is best explained by (1) a contract between the Company and its parent bottlers that encouraged retail price maintenance, (2) a single-coin vending machine technology, which limited the Company's price adjustment options due to limited availability and unreliability of the existing flexible price adjustment technologies, and (3) a single-coin monetary transaction technology, which limited the Company's price adjustment options due to the customer “inconvenience cost.” We show that these price adjustment costs are of a different nature than the standard menu cost, and their estimates exceed the existing estimates by an order of magnitude. A possible broader relevance of the nickel Coke phenomenon is discussed in the context of Nickel and Dime Stores, which were popular in the US in the late 1800s and the early 1900s.
Keywords: D40; E12; E31; L10; L11; L16; M10; M31; N1; N8; 330; Sticky Prices; Cost of Adjustment; Menu Cost; Retail Price Maintenance; Single-Coin Vending Machine; Customer Inconvenience Cost; Coca-Cola; Coke; Nickel Coke; Pepsi; Nickel and Dime Stores